The Representation of Pride in Poems of Al-Mutanabbi - Hikmal Haydar Raihan; R. Myrna Nur Sakinah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Al-Mutanabbi is widely recognized as one of the greatest poets in classical Arabic literature, whose works are distinguished by their linguistic richness and profound exploration of human experiences. Among the dominant themes in his poetry is pride, which reflects his identity, courage, and sense of honor. This study aims to analyze the representation of pride in selected poems of Al-Mutanabbi. The research employs a descriptive qualitative method with a literary approach. The data consist of three poems: The Poet Glories in His Own Youthful Prowess, At the Siege of Antioch, and The Poet Reproaches Saif al-Daula. Data were collected through close reading and note-taking techniques and analyzed by identifying, classifying, and interpreting textual evidence related to the representation of pride. The findings reveal that pride is represented through three categories: pride through self-glorification, pride through heroism, and pride through self-respect. Among these categories, self-glorification appears most frequently, reflecting Al-Mutanabbi's tendency to construct an image of himself as an extraordinary individual through expressions of superiority, courage, and honor. These findings contribute to a deeper understanding of the representation of pride in Al-Mutanabbi's poetry and provide an alternative perspective for the study of classical Arabic literature.